On the issue of improving the reliability of the cylinder head of the diesel engine - I. V. Sirotenko; E. E. Kossov (Вестник Научно-исследовательского института железнодорожного транспорта, 2020)
Cylinder head in a modern diesel engine is one of the most complex structurally loaded parts of its cylinder-piston group. The cylinder head is one of the most damaged units that determine the terms of scheduled repairs of the entire engine and, ultimately, the level of costs to maintain its performance. Article gives a review of studies on the cylinder head refinement of a diesel engine 5D49 (ChN26/26), and especially its main part which is the fire deck of the combustion chamber. Design disadvantage of the fire deck is the close location of the holes of the exhaust and intake valves, the inclined location of the nozzle. Depending on the heating and on the degree of constraint of the deformation of the head element, i. e. the absence of its free expansion, during heat exchange the process of destruction of the fire deck elements proceeds, which is characterized by the accumulation of fatigue damage in the material and plastic deformations. Studies have shown that under stationary loading conditions with the same scale of alternation of heating and cooling, the head should provide failure-free and durable operation. The occurrence of cracks due to the accumulation of residual stress should be attributed to the share of random "bursts" of temperature and temperature stresses arising during transient processes. These processes occupy approximately 20 % of the total engine operating time. One of the main reserves for improving the reliability of heads is to prevent exceeding thermal loads in operation by optimizing transient processes and increasing the uniformity of cylinder loading. The cylinder head of the 5D49 (ChN26/26) diesel engine type, apparently, has outlive the possibilities for a significant increase in reliability and service life and bringing it into line with operational requirements. For use on new engines, a new head must be developed — symmetrical with a central vertical arrangement of the nozzle, and with a well-thought-out cooling circuit.